2016
DOI: 10.1038/ajg.2016.256
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Impedance Monitoring: Clinical Pearls and Pitfalls

Abstract: The development of intraluminal esophageal impedance monitoring has improved our ability to detect and measure gastroesophageal reflux without dependence on acid content. This ability to detect previously unrecognized weak or nonacid reflux episodes has had important clinical implications in the diagnosis and management of gastroesophageal reflux disease (GERD). In addition, with the ability to assess bolus transit within the esophageal lumen, impedance monitoring has enhanced the recognition and characterizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 97 publications
(107 reference statements)
1
19
0
1
Order By: Relevance
“…In brief, impedance is the measure of the degree to which an electric circuit resists to an alternating electric current when impressed through tissue (21). Mucosal impedance reflects how electricity travels through intestinal tissue (22).…”
Section: Methodsmentioning
confidence: 99%
“…In brief, impedance is the measure of the degree to which an electric circuit resists to an alternating electric current when impressed through tissue (21). Mucosal impedance reflects how electricity travels through intestinal tissue (22).…”
Section: Methodsmentioning
confidence: 99%
“…2) A catheter-based MII-pH monitoring will cause the patient’s poor tolerance for monitoring pH-impedance [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…3) Dietary changes during the MI-pH evaluation may lead to a poor predictor of gastroesophageal reflux [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is still available in only a small number of centres and is not part of the mainstream toolkit used by most gastroenterologists. A recent systematic review of pH impedance concluded that important clinical and technical shortcomings limit its diagnostic value and must be considered when interpreting study results . In contrast to earlier versions, the Rome IV criteria include patients with physiological acid exposure in the distal oesophagus and an abnormal SAP in the definition of functional heartburn .…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of pH impedance concluded that important clinical and technical shortcomings limit its diagnostic value and must be considered when interpreting study results. 29 In contrast to earlier versions, the Rome IV criteria include patients with physiological acid exposure in the distal oesophagus and an abnormal SAP in the definition of functional heartburn. 30 This modification to the Rome criteria needs validation, but it should be noted that the number of patients with physiological acid exposure and a positive symptom association probability in our study was too small to influence the results.…”
Section: Discussionmentioning
confidence: 99%